Diversity of chlorobiphenyl-metabolizing bacteria and their biphenyl dioxygenases in contaminated sediment - Koubek, Jiri; Mackova, Martina; Macek, Tomas; Uhlik, Ondrej (Chemosphere, 2013)
Bacteria and bacterial communities in sites contaminated with polychlorinated biphenyls have been extensively studied in the past decades. However, there are still major gaps in the knowledge of environmental processes, especially in the behavior of previously described bacteria in vitro, their real degradation abilities and the enzymes that are involved in the degradation processes. In this work we analyzed actively degrading bacterial populations by stable isotope probing with (13)C biphenyl and (13)C-4-chlorobiphenyl as labeled substrates in the environment of sediment contaminated with polychlorinated biphenyls. We performed analysis of populations which degrade biphenyl and 4-chlorobiphenyl at concentrations similar to those of the original site. Several bacterial genera were revealed to actively participate in biphenyl and 4-chlorobiphenyl removal, some of which had not previously been described to take part in this process. We also found there are few differences in the communities metabolizing biphenyl and 4-chlorobiphenyl. Analysis of the genes responsible for substrate removal proved most of the genes to be closely related to Pseudomonas pseudoalcaligenes KF707 genes giving bacteria the ability of transforming di-para-chlorinated biphenyls.
Keywords: Molecular Sequence Data; Soil Microbiology; látky znečišťující půdu; Dioxygenases; Bacteria; polychlorované bifenyly; Biodegradation, Environmental; biodegradace; genetická variace; Geologic Sediments; Stable isotope probing; Bacteria metabolizing PCBs; Genetic Variation; geologické sedimenty; Base Sequence; sekvence nukleotidů; Soil Pollutants; Polychlorinated Biphenyls; dioxygenasy; půdní mikrobiologie; fylogeneze; Biphenyl dioxygenase; molekulární sekvence - údaje; 16S rRNA genes analysis; Phylogeny